METODE DAKWAH NABI SULAIMAN DALAM PERSPEKTIF AL QUR’AN - Afrizal El Adzim Syahputra (MIYAH : Jurnal Studi Islam, 2019)
Abstract: Dakwah is an appeal or invitation to conversion, or an attempt to changethe situation into a better and perfect situation, both for the person and society. Da'wah is one of the teachings of Islam that is obligated of its followers. Success and unsuccess in dakwah is determined by the ability of preachers to use the right methodes. Therefore, the Qur'an contains several methods of da'wah used by people and the previous prophets to invite their followers to become part of the religion of Allah. One of them, prophet Sulaiman methods, when he received information on the where abouts of Queen Balqis and his elders who worshiped the sun, he wanted to invite them to worship Allah SWT. In dakwah, prophet Sulaiman used several methods, including: using the preaching of correspondence, revealing the power and ability of prophet Sulaiman to them, firmly against the target of da'wah, not insulting / taunting the worshipers of the missionary objectives and using the demonstration method. By using that several methods, prophet Suliaman with the permission of Allah can draw the sympathy of Queen Balqis. In the end, she submits and declares her Islam in front of prophet Sulaiman.Key Words: Method, Dakwah, Prophet Sulaiman